2015
DOI: 10.2139/ssrn.2700089
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Distance and Foreign Direct Investment

Abstract: This paper studies the link between Foreign Direct Investment (FDI) and institutional distance. Using a heterogeneous firms framework, we develop a theoretical model to explain how institutional distance influences FDI and it is shown that institutional distance reduces both the likelihood that a firm will invest in a foreign country and the volume of investment it will undertake. We test our model, using inward and outward FDI data on OECD countries. The empirical results confirm the theory and indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
(29 reference statements)
5
23
0
Order By: Relevance
“…Indeed, while the number of contracts can be considered as a proxy for the number of firms involved in FLA, the amount of land proxies the size of the investments. The literature has shown that institutional distance reduces FDI through two distinct channels: by reducing the number of firms involved -the so-called extensive margin -and the size of investments -the intensive margin (Cezar, Escobar, 2015). We, therefore, check whether this also holds for FLA.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Indeed, while the number of contracts can be considered as a proxy for the number of firms involved in FLA, the amount of land proxies the size of the investments. The literature has shown that institutional distance reduces FDI through two distinct channels: by reducing the number of firms involved -the so-called extensive margin -and the size of investments -the intensive margin (Cezar, Escobar, 2015). We, therefore, check whether this also holds for FLA.…”
Section: Introductionmentioning
confidence: 88%
“…The literature has also shown that this impact differs depending on the country of origin of the investing firm and the destination country (developed versus developing countries). Indeed, this negative effect has been found to be lower for South-South FDI (Demir, Hu, 2016), for inward -with respect to outward -FDI in OECD countries (Cezar, Escobar, 2015), and for those developing countries endowed with large reserves of natural resources (Aleksynska, Havrylchyk, 2013).…”
Section: The Determinants Of Foreign Land Acquisitions: Backgroundmentioning
confidence: 99%
See 3 more Smart Citations